Sistem Informasi Sekolah Berbasis Web pada SMP Yapendak Tinjowan - Nora Junita Siallagan; Lamhot Sitorus (JUKI : Jurnal Komputer dan Informatika, 2019)
In an educational organization / institution the school information system is very important. But sometimes the information is slowly obtained. In academic handling such as registration of new students and student grades that are still done manually, causing slow processing of data processing and presentation of information to students, teachers and principals. To overcome this problem, a web-based School Information System was designed at Yapendak Middle School with the PHP programming language and MySQL database, so that new student registrations and student grades could be handled quickly. With the handling of this web-based School Information System, the processing of new student registration data and student grades can be handled quickly and the presentation of information quickly and accurately to students, teachers and principals.